Pemetaan Tren Pembelajaran Ekologi di Sekolah Menengah Pertama: Kajian Sistematis atas Strategi, Media, dan Kompetensi Siswa - Wicaksana, Dhafa Satrio Rizki; Amelia, Rizki Nor (Journal of Natural Sciences, 2025)
This study aims to map trends in ecology learning at the junior high school level based on learning strategies, learning media, and student competencies. The method used is a Systematic Literature Review (SLR) with a PRISMA approach applied to 30 articles published between 2015 and 2025, selected according to inclusion and exclusion criteria. The analysis was conducted descriptively and quantitatively to examine the frequency and tendencies of each aspect. The results show that learning strategies constitute the most dominant category (40%), followed by learning media (33%) and student competencies (27%). The most frequently used strategies are Problem-Based Learning (PBL) and Inquiry, with worksheets (LKPD) and e-modules serving as effective media for improving students’ scientific literacy and critical thinking skills. The study concludes that trends in ecology learning at the junior high school level are oriented toward constructivist, problem-based, and technology-driven approaches.